The European Union and Internal Security - Mitsilegas, V. author. aut Link
VI, 203 p.
Keywords: In the post-Cold war period new security threats have arisen in Western Europe. Amongst these, organized crime and illegal immigration are acknowledged to represent significant security challenges. The European Union and Internal Security analyses the nature of these challenges and investigates how the EU has been evolving to counter them. Written by experts in the fields of political science and law, this book addresses a hitherto neglected area of study.